WASP (Write a Scientific Paper): The role of the pathology department in clinical research. (January 2019) - Cuschieri, Sarah; Grech, Victor; Barbara, Christopher
Abstract: The pathology laboratory is the hub of investigatory medical care, and constitutes an invaluable asset for clinical research. A number of disciplines fall under the cap of a pathology laboratory. Researchers may gain access to such services provided ethical and laboratory administrative permissions have been granted. While establishing the research budget it is essential to have a clear understanding of what goes on behind the path lab curtains as this may impinge on what can and cannot be done, financially and otherwise. Indeed, the process is far more complex than just handing a specimen and obtaining the respective result. Infrastructure, material and human resources need to be quantified and their respective costing identified. Liaison with the laboratory section personnel facilitates the smooth provision of service and research outcomes.